THE ANALYSIS OF FLOUTING MAXIM IN MATA NAJWA’S TALKSHOW ‘GENGSI MEREBUT KURSI’ - DEVIAN TRY GUSTARY (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2018)
The study is aimed at analysing the flouting of Grice’s Cooperative Principles and finding out the implicature of the flouting maxims. Descriptive qualitative method was employed. The data were analyzed by identifying the utterances based on Grice’s Cooperative Principle proposed by Grice (1975), classifying the flouting of maxims and finding the maxim that was mostly flouted in the video of Mata Najwa talk show. The findings show that the guest speaker of the show flouted all the maxims. The guest speaker flouted maxims through six manners that are giving more and lack information, saying something that lack of evidence, giving irrelevance responses, saying something ambiguous/unclear and giving unnecessary prolixity (verbosity). The study reveals that there are 1 occurrence of flouting the maxim of quality, 9 occurrences of flouting the maxim of quantity, 13 occurrences of flouting the maxim of manner, and 6 occurrences of flouting the maxim of quality. Maxim of manner is the most often flouted as it is indicated by obscure and unclear responses